Influence of Augmented Reality (AR) Technology via Mobile Application for Knowledge Transfer Program in Fourth Industrial Revolution Era - Wong, Seng Yue; Abdullah, Zuraidah; Haq Hussin, Muhamad Saiful; Kadri, Nahrizul Adib; Obaidellah, Unaizah; Mohd Zubir, Nashrul (ASEAN Journal of Community Engagement, 2021)
Education is considered one of the impact sectors, which is a part of the Industrial Revolution 4.0 (IR4.0), where humanity and technology are aligned to empower new possibilities. Academic exploration of Augmented Reality (AR) technology and skills of IR 4.0 in schools, especially in rural areas, have been scarce. Therefore, this paper examines the influence of AR technology via mobile application on teachers and students via community-based learning approach. One rural primary school was selected for this community-based research project: Sekolah Kebangsaan Pulau Gaya in Kota Kinabalu, Sabah, Malaysia. It was selected as the school’s drop-out rates have remained high and it has low student retention levels. Students here are unprepared for becoming more autonomous learners with better responsibility for organizing and planning their learning time. There were 22 teachers and 95 primary students (75 female and 20 male), aged from nine to twelve, third to sixth grades involved in this project. Their changes in attitude, practices, and skills were evaluated before and after the AR intervention. A majority showed an increase in positive preferences and enjoyment in AR learning, and in general, an increase in their STEM skills and performance. The findings show that employing an AR approach in primary students learning reveal significant differences in students’ preference in AR learning, enjoyment in AR learning, performance in STEM learning, enjoyment in science learning, willingness to attend STEM classes, and STEM skills after the AR intervention. Thus, the newly developed AR learning module is an attempt to assist teachers nurture their students via this knowledge transfer program, increase their engagement, peer interactions and collaboration, and improve their confidence to become successful learners in the future.